Mucocutaneous cysts in the newborn. - V, Vijay; Singh, Yogindher; Selvam, Oviya; R, Senthilkumaran; I, Dinesh; Prasanna, Aravind; Karunanandhan, Manobalan (European Journal of Pediatric Dermatology, 2025)
Mucocutaneous cystic lesions in newborns are common and benign findings that often cause unwarranted concern due to their unusual locations. This case series highlights four distinct presentations: congenital milia, Epstein pearls (oral and penile), Bohn’s nodules, and smegma pseudocysts, emphasizing their clinical and dermoscopic features. Awareness of these physiological lesions is essential to avoid misdiagnoses, reassure parents, and prevent unnecessary interventions.